MicroRNA regulation of critical retinal pigment epithelial functions. Issue 1 (January 2022) - Du, Samuel W.; Palczewski, Krzysztof
Abstract : MicroRNAs are short, evolutionarily conserved noncoding RNAs that are critical for the control of normal cellular physiology. In the retina, photoreceptors are highly specialized neurons that transduce light into electrical signals. Photoreceptors, however, are unable to process visual stimuli without the support of the retinal pigment epithelium (RPE). The RPE performs numerous functions to aid the retina, including the generation of visual chromophore and metabolic support. Recent work has underscored how microRNAs enable vision through their contributions to RPE functions. This review focuses on the biogenesis and control of microRNAs in rodents and humans, the roles microRNAs play in RPE function and degeneration, and how microRNAs could serve as potential therapeutics and biomarkers for visual diseases. Highlights: The retinal pigment epithelium (RPE) is crucial for maintaining photoreceptor and neural retinal health. Dysregulation of this postmitotic monolayer leads to retinal degeneration in various diseases such as age-related macular degeneration. MicroRNAs have been shown to regulate the gene expression of many vital RPE pathways. These include oxidative stress and metabolism, phagocytosis and endolysosomal function, exosomes and intercellular signaling, and vascular homeostasis. RPE development has been shown to be heavily dependent on the correct expression of microRNAs and their processing machinery, and altered microRNA levels can suppress differentiation or promote dedifferentiation of the RPE. Perturbations in the levels or composition of RPE microRNAs lead to RPE dysfunction and the progression of disease, revealing potential targets for therapeutic and biomarker development.